Detecting Fraudulent Financial Reporting Through External Auditors With Supporting Audit Evidence - Tono Hartono; Susanto Salim (UNIVED Press, 2026)
Study This aim For know How proof support that can be used by the parties external auditor in detect fraud reporting finance That the research​ This highlight various fraud in report finance like manipulate report finance , the existence of error recording , deviation assets , corruption. Therefore, the external auditor plays a role in uncovering financial statement fraud based on supporting evidence found by the external auditor. The external auditor must also be professional and not believe anything conveyed by company management without clear supporting evidence. This method requires internal control tests in conducting audits. The required supporting evidence is a transaction logbook, clear supporting evidence, and the person responsible for the issued transactions. This study needs to review various cases of fraud that are real and have occurred in Indonesia. Therefore, this study needs to emphasize the importance of auditor independence and integrity in carrying out audit duties.